Catalyst for preparing morpholine by diethylene glycol method and preparation method thereof
By using the Ni-Cu@Y3Si2C2-SiC catalyst prepared by the Y3Si2C2-SiC multi-layer ceramic support and nickel-copper precursor, the problems of low production efficiency and high energy consumption of morpholine synthesis in the prior art were solved, and the effects of high catalytic activity and good stability were achieved.
Patent Information
- Application Number
- CN202111455111.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-11-29
AI Technical Summary
In the prior art, when diethylene glycol catalytic ammonia cyclization is used for morpholine synthesis, the production efficiency is low, the energy consumption is high, and the catalytic performance and stability of the catalyst need to be improved.
Y3Si2C2-SiC multi-layer ceramic support was prepared by molten salt and SiC by sintering with SPS, and the precursors of nickel and copper were arranged into aqueous solutions. The Ni-Cu@Y3Si2C2-SiC catalyst was prepared by immersion, filtration, drying, reducing and calcining.
It improves the catalytic activity and stability of the catalyst, simplifies the preparation process, reduces energy consumption, and is suitable for industrial production.
Smart Images

Figure CN116173995B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and specifically discloses a catalyst for preparing morpholine by a diethylene glycol method and a preparation method thereof. Background Art
[0002] Morpholine, also known as morpholine or 1,4-oxazacyclohexane, has the molecular formula C4H9NO and is one of the important cyclic amines for industrial use. It is a colorless, water-absorbing oily liquid and a mild base. Morpholine contains secondary amine groups and has all the typical reaction characteristics of secondary amine groups. It reacts with inorganic acids to form salts and with organic acids to form salts or amides. It can undergo alkylation reactions and can also react with ethylene oxide, ketones or undergo Willgerodt reactions. Due to its characteristics of nitrogen-oxygen heterocycles, morpholine occupies an important position in chemical production and is an intermediate in the manufacture of many fine chemical products. It has become one of the fine petrochemical products with important commercial uses. It can be used to prepare rubber vulcanization accelerators and rust inhibitors such as NOBS (N-oxydiethylene-2-thiazolesulfonamide) and OTOS (monooxydiethylenecarbamoyl-N-oxydiethylenesulfonamide), preservatives, surfactants, descaling agents, analgesics, local anesthetics, fruit preservatives, textile printing and dyeing auxiliaries, etc. It is widely used in the fields of rubber, medicine, pesticides, dyes, coatings, etc.
[0003] The synthetic route of morpholine can be divided into diethanolamine dehydration method, dicyanomethyl ether catalytic hydrogenation method, ethylene oxide catalytic amination method, dichloroethyl ether dechlorination amination cyclization method, amine dehydration cyclization method, diethylene glycol catalytic ammonia decyclization method, etc., depending on the raw materials used. Among them, the diethylene glycol catalytic ammonia decyclization method has the advantages of easy availability of raw materials, low price, low toxicity, and less generation of three wastes, and is very suitable for industrial large-scale production. Domestic manufacturers basically use this method.
[0004] However, the diethylene glycol catalytic ammonolysis cyclization method has low production efficiency and high energy consumption. To reduce the energy consumption and cost of morpholine synthesis, it is necessary to prepare a catalyst with excellent performance and suitable for different process routes and raw material routes. The carrier of the current morpholine catalyst mostly adopts nanoparticles such as γ-Al2O3, MgO or ZnO or the inorganic nanomaterials formed by composite formation, such as the patents of CN200510090149.4, CN201410186330.4 and CN201110428997.7 of application numbers. The catalytic performance and stability of the above catalysts are yet to be improved. Summary of the invention
[0005] The purpose of the present invention is to solve one of the technical problems existing in the prior art. To this end, the embodiment of the present invention needs to provide a catalyst for preparing morpholine by a diethylene glycol method and a preparation method thereof.
[0006] The specific technical solutions adopted by the present invention are as follows:
[0007] 1) using yttrium-containing salt and SiC to prepare a Y3Si2C2-SiC multilayer ceramic carrier by molten salt method and SPS sintering;
[0008] 2) preparing a nickel metal precursor and a copper metal precursor into an aqueous solution, and immersing the Y3Si2C2-SiC multilayer ceramic carrier into the aqueous solution in a reaction kettle;
[0009] 3) After the impregnation, the product is filtered, dried, reduced in H2 atmosphere, and calcined to obtain a multilayer ceramic nickel-copper Ni-Cu@Y3Si2C2-SiC catalyst.
[0010] Further, the preparation process of the Y3Si2C2-SiC multilayer ceramic carrier is as follows:
[0011] 1) heating and melting a yttrium-containing salt, SiC and sodium chloride at a certain temperature according to the molar ratio of each element of Y3Si2C2, then washing the product with deionized water until it is neutral, and vacuum drying to obtain a product 1; preferably, the yttrium-containing salt is yttrium nitrate hexahydrate, the reaction temperature is 580-620°C, and the reaction time is 1.5-2.5h; more preferably, the reaction temperature is 600°C, and the reaction time is 2h;
[0012] 2) The product is crushed and mixed with SiC at a molar ratio of 1:4, and then SPS sintered to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering is carried out in an Ar atmosphere; preferably, the SPS sintering temperature is 880-920°C, the sintering time is 8-12 minutes, and the sintering pressure is 48-52MPa; more preferably, the SPS sintering temperature is 900°C, the sintering time is 10 minutes, and the sintering pressure is 50MPa. The SPS sintering reaction is very rapid, and the temperature difference, reaction time difference, and reaction pressure difference have a great influence on the product performance, so the reaction conditions need to be strictly controlled.
[0013] Furthermore, the precursor of the nickel metal is selected from nickel nitrate, nickel sulfate, nickel acetate or other water-soluble nickel salts, and the precursor of the copper metal is selected from copper nitrate, copper sulfate, copper acetate or other water-soluble copper salts.
[0014] Furthermore, the immersion temperature is 80-100° C., the immersion time is 12-24 hours, and the immersion process is carried out in a continuous stirring manner in the early stage.
[0015] Further, the drying temperature is 80-120°C, and the reduction temperature is 480-520°C; preferably, the drying temperature is 100°C, and the reduction temperature is 500°C.
[0016] Furthermore, the calcination temperature is 580-620° C., the calcination time is 4-6 hours, and the calcination atmosphere is a nitrogen atmosphere.
[0017] Furthermore, the Y3Si2C2-SiC multilayer ceramic carrier is in powder, granular, or extruded strip or block form.
[0018] Furthermore, the components of the catalyst are calculated by weight percentage: the Y3Si2C2-SiC multilayer ceramic carrier is 75% to 80%, Cu is 10% to 12%, and Ni is 10% to 15%.
[0019] Furthermore, the inner surfaces of the first liner and the second liner used in the reactor are both provided with impact pieces; preferably, the impact pieces are spiral ridges or spiral grooves provided on the inner surfaces of the linings; more preferably, pits are provided on the spiral ridges, or bumps are provided on the spiral grooves.
[0020] Another object of the present invention is to provide a catalyst for preparing morpholine by a diethylene glycol process, wherein the catalyst is prepared by the method described in any one of claims 1 to 9.
[0021] The beneficial effects of the present invention are:
[0022] 1. The catalyst carrier in this application is prepared by molten salt method plus SPS sintering, which has a simple preparation method, low energy consumption, and is suitable for industrial production applications; compared with the direct use of molten salt method to prepare Y3Si2C2-SiC multilayer ceramics, it avoids the high melting temperature that makes the multilayer ceramics densified and the porosity reduced, and the specific surface area of the carrier reduced; SPS sintering is simple to operate, short in time, fast in sintering, and low in energy consumption;
[0023] 2. After the carrier is prepared, the factors affecting the performance of the catalyst are largely determined by the loading of the active component on the carrier and the content of the active component. This requires good control of the process parameters of the impregnation and the calcination. The process and parameters in this application are used to obtain a catalyst with high catalytic activity and good stability.
[0024] 3. The Y3Si2C2-SiC multilayer ceramic carrier is in the form of powder, granules, or extruded strips or blocks. These carriers are not too large and can quickly adsorb active component ions in the impregnation solution. They are also easy to collide with the reactor lining and be crushed under stirring.
[0025] 4. The reactor of the present application can use the spiral impact piece on the liner to impact and crush the carrier when preparing the catalyst, which is convenient for loading the active components and saves the time and energy consumption of impregnation loading; the spiral impact piece also facilitates the solution to flow to the inner liner during stirring, and is also convenient for cleaning; the setting of pits and convex points increases the impact points, further increasing the impact on the particles in the reaction solution;
[0026] 5. The catalyst prepared in this application has high catalytic activity and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic diagram of the structure of the first lining of the reactor in an embodiment of the present invention. Figure 1 ;
[0028] Figure 2 This is a schematic diagram of the structure of the second lining of the reactor in an embodiment of the present invention. Figure 2 ;
[0029] Figure 3 It is the chromatogram of the gas phase detection result after the reaction of Example 1.
[0030] In the figure, 101 is a first lining; 102 is a spiral ridge; 103 is a pit; 201 is a second lining; 202 is a spiral groove; 203 is a convex point. DETAILED DESCRIPTION
[0031] The preparation method of the catalyst of the present invention is:
[0032] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0033] 1) Weighing hydrated yttrium nitrate and SiC according to the molar ratio of each element in Y3Si2C2, heating the hydrated yttrium nitrate, SiC and sodium chloride at a certain temperature of 580-620°C to melt and react for 1.5-2.5h, then washing the product with deionized water until it is neutral, and vacuum drying to obtain product 1;
[0034] 2) The product 1 is crushed and mixed with SiC in a molar ratio of 1:4, and then subjected to SPS sintering to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS is carried out in an Ar atmosphere, the SPS sintering temperature is 880-920°C, the sintering time is 8-12 min, and the sintering pressure is 48-52 MPa.
[0035] (2) Preparation of catalyst:
[0036] 1) Weighing the Y3Si2C2-SiC multilayer ceramic carrier obtained in step (1), a nickel metal precursor and a copper metal precursor in a proportion of 75% to 80% by weight of the Y3Si2C2-SiC multilayer ceramic carrier, 10% to 12% by weight of Cu and 10% to 15% by weight of Ni;
[0037] 2) crushing the Y3Si2C2-SiC multilayer ceramic carrier into powder, granules, or extruded strips or blocks;
[0038] 3) Preparing a nickel metal precursor and a copper metal precursor into an aqueous solution and pouring the aqueous solution into a reactor, and then impregnating the Y3Si2C2-SiC multilayer ceramic carrier obtained in step 2) into the reactor, the impregnation temperature is 80-100° C., the impregnation time is 12-24 hours, and the impregnation process is carried out in a continuous stirring manner in the early stage;
[0039] 4) The impregnated product is then dried at 100°C, reduced in a 500°C H2 atmosphere, and then calcined at 580-620°C for 4-6 hours in a nitrogen atmosphere to obtain a Ni-Cu catalyst loaded on a Y3Si2C2-SiC multilayer ceramic.
[0040] The precursor of the nickel metal is selected from nickel nitrate, nickel sulfate, nickel acetate or other nickel salts soluble in water, and the precursor of the copper metal is selected from copper nitrate, copper sulfate, copper acetate or other copper salts soluble in water.
[0041] See also Figure 1 , Figure 2 In order to improve the efficiency of the preparation method and reduce the particle size of the obtained catalyst, we have improved the first liner 101 and the second liner 201 used in the reactor. The first liner 101 and the second liner 201 of the reactor used in this application are provided with impact pieces on the inner surface, so that the reaction solution will collide with the impact piece during the stirring process, and the particles in the reaction solution will be rebounded and the particles will be broken, thereby reducing the size of the particles, increasing the specific surface area of the carrier, and facilitating the deposition of active components. Preferably, the impact piece is a plurality of annular ridges or grooves arranged on the inner surface of the liner, and further preferably, the impact piece is a spiral ridge 102 or a spiral groove 202. The spiral structure facilitates the reaction liquid after the impact to flow down along the spiral structure, and also facilitates the clarity of the liner in the later stage; more preferably, the spiral ridge is provided with pits 103, or the spiral groove is provided with convex points 203, and the pits and convex points increase the impact points, further increasing the impact on the particles in the reaction liquid.
[0042] Example 1
[0043] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0044] 1) 72 g of hydrated yttrium nitrate, 5 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated at 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0045] 2) The product 1 was crushed into fine powder and mixed with 20 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier. The SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0046] (2) Catalyst preparation:
[0047] 1) crushing the Y3Si2C2-SiC multilayer ceramic carrier prepared in (1) into particles;
[0048] 2) Weigh 35.53 g of copper nitrate and 34.58 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0049] 3) immersing the particles in 1) into the mixed solution in 2) at 90° C. for 18 hours, with continuous stirring at the initial stage of the immersion process;
[0050] 4) The impregnation product was filtered, and the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 600° C. in a muffle furnace in a nitrogen atmosphere for 5 h to obtain a supported metal catalyst.
[0051] Example 2
[0052] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0053] 1) 80.43 g of hydrated yttrium nitrate, 5.6 g of SiC and 30 g of NaCl were placed in an alumina crucible, heated at 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0054] 2) The product 1 was crushed into fine powder and mixed with 22.4 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0055] (2) Catalyst preparation:
[0056] 1) crushing the Y3Si2C2-SiC multilayer ceramic carrier prepared in (1) into particles;
[0057] 2) Weigh 29.92 g of copper nitrate and 30.94 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0058] 3) immersing the particles in 1) into the mixed solution in 2) at 90° C. for 18 hours, with continuous stirring at the initial stage of the immersion process;
[0059] 4) The impregnation product was filtered, and the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 600° C. in a muffle furnace in a nitrogen atmosphere for 5 h to obtain a supported metal catalyst.
[0060] Example 3
[0061] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0062] 1) 76.6 g of hydrated yttrium nitrate, 5.33 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated to 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0063] 2) The product 1 was crushed into fine powder and mixed with 21.33 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier. The SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0064] (2) Catalyst preparation:
[0065] 1) crushing the Y3Si2C2-SiC multilayer ceramic carrier prepared in (1) into particles;
[0066] 2) Weigh 32.73 g of copper nitrate and 39.13 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0067] 3) immersing the particles in 1) into the mixed solution in 2) at 90° C. for 18 hours, with continuous stirring at the initial stage of the immersion process;
[0068] 4) The impregnation product was filtered, and the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 600° C. in a muffle furnace in a nitrogen atmosphere for 5 h to obtain a supported metal catalyst.
[0069] Example 4
[0070] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0071] 1) 76.6 g of hydrated yttrium nitrate, 5.33 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated to 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0072] 2) The product 1 was crushed into fine powder and mixed with 21.33 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0073] (2) Catalyst preparation:
[0074] 1) crushing the Y3Si2C2-SiC multilayer ceramic carrier prepared in (1) into particles;
[0075] 2) Weigh 32.73 g of copper nitrate and 39.13 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0076] 3) immersing the particles in 1) into the mixed solution in 2) at 80° C. for 18 hours, with continuous stirring at the initial stage of the immersion process;
[0077] 4) The impregnation product was filtered, and the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 600° C. in a muffle furnace in a nitrogen atmosphere for 5 h to obtain a supported metal catalyst.
[0078] Example 5
[0079] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0080] 1) 76.6 g of hydrated yttrium nitrate, 5.33 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated to 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0081] 2) The product 1 was crushed into fine powder and mixed with 21.33 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0082] (2) Catalyst preparation:
[0083] 1) crushing the Y3Si2C2-SiC multilayer ceramic carrier prepared in (1) into particles;
[0084] 2) Weigh 32.73 g of copper nitrate and 39.13 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0085] 3) immersing the particles in 1) into the mixed solution in 2) at 100° C. for 18 hours, with continuous stirring at the initial stage of the immersion process;
[0086] 4) The impregnation product was filtered, and the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 600° C. in a muffle furnace in a nitrogen atmosphere for 5 h to obtain a supported metal catalyst.
[0087] Example 6
[0088] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0089] 1) 76.6 g of hydrated yttrium nitrate, 5.33 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated to 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0090] 2) The product 1 was crushed into fine powder and mixed with 21.33 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0091] (2) Catalyst preparation:
[0092] 1) crushing the Y3Si2C2-SiC carrier prepared in (1) into particles;
[0093] 2) Weigh 32.73 g of copper nitrate and 39.13 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0094] 3) immersing the particles in 1) into the mixed solution in 2) at 90° C. for 12 h, with continuous stirring at the initial stage of the immersion process;
[0095] 4) After the impregnation, the solution was filtered, the filter cake was dried in an oven at 100°C for 5 h, reduced at 500°C in a hydrogen atmosphere, and then calcined at 600°C in a muffle furnace in a nitrogen atmosphere for 5 h to obtain a supported metal catalyst.
[0096] Example 7
[0097] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0098] 1) 76.6 g of hydrated yttrium nitrate, 5.33 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated to 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0099] 2) The product 1 was crushed into fine powder and mixed with 21.33 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0100] (2) Catalyst preparation:
[0101] 1) crushing the Y3Si2C2-SiC carrier prepared in (1) into particles;
[0102] 2) Weigh 32.73 g of copper nitrate and 39.13 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0103] 3) immersing the particles in 1) into the mixed solution in 2) at 90° C. for 24 hours, with continuous stirring at the initial stage of the immersion process;
[0104] 4) The impregnation product was filtered, and the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 600° C. in a muffle furnace in a nitrogen atmosphere for 5 h to obtain a supported metal catalyst.
[0105] Example 8
[0106] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0107] 1) 76.6 g of hydrated yttrium nitrate, 5.33 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated to 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0108] 2) The product 1 was crushed into fine powder and mixed with 21.33 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0109] (2) Catalyst preparation:
[0110] 1) crushing the Y3Si2C2-SiC carrier prepared in (1) into particles;
[0111] 2) Weigh 32.73 g of copper nitrate and 39.13 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0112] 3) immersing the particles in 1) into the mixed solution in 2) at 90° C. for 18 hours, with continuous stirring at the initial stage of the immersion process;
[0113] 4) The impregnation product was filtered, and the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 580° C. in a muffle furnace in a nitrogen atmosphere for 5 h to obtain a supported metal catalyst.
[0114] Example 9
[0115] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0116] 1) 76.6 g of hydrated yttrium nitrate, 5.33 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated to 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0117] 2) The product 1 was crushed into fine powder and mixed with 21.33 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0118] (2) Catalyst preparation:
[0119] 1) crushing the Y3Si2C2-SiC carrier prepared in (1) into particles;
[0120] 2) Weigh 32.73 g of copper nitrate and 39.13 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0121] 3) immersing the particles in 1) into the mixed solution in 2) at 90° C. for 18 hours, with continuous stirring at the initial stage of the immersion process;
[0122] 4) The impregnation product was filtered, and the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 620° C. in a muffle furnace in a nitrogen atmosphere for 5 h to obtain a supported metal catalyst.
[0123] Example 10
[0124] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0125] 1) 76.6 g of hydrated yttrium nitrate, 5.33 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated to 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0126] 2) The product 1 was crushed into fine powder and mixed with 21.33 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0127] (2) Catalyst preparation:
[0128] 1) crushing the Y3Si2C2-SiC carrier prepared in (1) into particles;
[0129] 2) Weigh 32.73 g of copper nitrate and 39.13 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0130] 3) immersing the particles in 1) into the mixed solution in 2) at 90° C. for 18 hours, with continuous stirring at the initial stage of the immersion process;
[0131] 4) The impregnation product was filtered, and the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 600° C. in a muffle furnace in a nitrogen atmosphere for 4 h to obtain a supported metal catalyst.
[0132] Embodiment 11
[0133] (1) Preparation of Y3Si2C2-SiC multilayer ceramic carrier:
[0134] 1) 76.6 g of hydrated yttrium nitrate, 5.33 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated to 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0135] 2) The product 1 was crushed into fine powder and mixed with 21.33 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0136] (2) Catalyst preparation:
[0137] 1) crushing the Y3Si2C2-SiC carrier prepared in (1) into particles;
[0138] 2) Weigh 32.73 g of copper nitrate and 39.13 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0139] 3) immersing the particles in 1) into the mixed solution in 2) at 90° C. for 18 hours, with continuous stirring at the initial stage of the immersion process;
[0140] 4) The impregnation product was filtered, and the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 600° C. in a muffle furnace in a nitrogen atmosphere for 6 h to obtain a supported metal catalyst.
[0141] Comparative Example 1
[0142] (1) Preparation of Y3Si2C2-SiC carrier:
[0143] 1) 38.3 g of hydrated yttrium nitrate, 5 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated at 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0144] 2) The product 1 was crushed into fine powder and mixed with 20 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0145] (2) Catalyst preparation:
[0146] 1) crushing the Y3Si2C2-SiC carrier prepared in (1) into particles;
[0147] 2) Weigh 35.53 g of copper nitrate and 34.58 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0148] 3) immersing the particles in 1) into the mixed solution in 2) at 90° C. for 18 hours, with continuous stirring at the initial stage of the immersion process;
[0149] 4) The impregnation product was filtered, and the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 600° C. in a muffle furnace in a nitrogen atmosphere for 5 h to obtain a supported metal catalyst.
[0150] Comparative Example 2
[0151] (1) Preparation of Y3Si2C2-SiC carrier:
[0152] 1) 114.9 g of hydrated yttrium nitrate, 5.6 g of SiC and 30 g of NaCl were placed in an alumina crucible, and heated at 600° C. for melting reaction for 2 h. The whole process was carried out under argon protection. The reaction product was then cooled and washed with deionized water until neutral, and vacuum dried to obtain product 1;
[0153] 2) The product 1 was crushed into fine powder and mixed with 22.4 g SiC, and SPS sintered in an Ar atmosphere to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering temperature was 900°C, the sintering time was 10 min, and the sintering pressure was 50 MPa.
[0154] (2) Catalyst preparation:
[0155] 1) crushing the Y3Si2C2-SiC multilayer ceramic carrier prepared in (1) into particles;
[0156] 2) Weigh 29.92 g of copper nitrate and 30.94 g of nickel nitrate and dissolve them in deionized water in a reaction kettle to prepare a mixed solution;
[0157] 3) immersing the particles in 1) into the mixed solution in 2) at 90° C. for 18 hours, with continuous stirring at the initial stage of the immersion process;
[0158] 4) After the impregnation, the solution was filtered, the filter cake was dried in an oven at 100° C. for 5 h, reduced at 500° C. in a hydrogen atmosphere, and then calcined at 600° C. in a muffle furnace in a nitrogen atmosphere for 5 h to obtain a supported metal catalyst.
[0159] Comparative Example 3
[0160] The difference between this embodiment and embodiment 3 is that the immersion temperature in this embodiment is 200°C.
[0161] Comparative Example 4
[0162] The difference between this embodiment and embodiment 3 is that the immersion temperature in this embodiment is 50°C.
[0163] Comparative Example 5
[0164] The difference between this embodiment and embodiment 3 is that the immersion time in this embodiment is 8 hours.
[0165] Comparative Example 6
[0166] The difference between this embodiment and embodiment 3 is that the immersion temperature in this embodiment is 50 hours.
[0167] Comparative Example 7
[0168] The difference between this embodiment and embodiment 3 is that the calcination temperature in this embodiment is 550°C.
[0169] Comparative Example 8
[0170] The difference between this embodiment and embodiment 3 is that the calcination temperature in this embodiment is 650°C.
[0171] Comparative Example 9
[0172] The difference between this embodiment and embodiment 3 is that the calcination time in this embodiment is 3 hours.
[0173] Comparative Example 10
[0174] The difference between this embodiment and embodiment 3 is that the calcination temperature in this embodiment is 7h.
[0175] Catalyst activity evaluation:
[0176] In a stainless steel fixed bed reactor with an inner diameter of 10 mm, 5 mL of catalyst was placed in the constant temperature zone of the reaction tube, and the catalyst was reduced and activated with a mixture of 20% hydrogen and 80% nitrogen, and then the diethylene glycol gas phase method for synthesizing morpholine was carried out. The reaction conditions were: reaction temperature 220°C, reaction pressure 2.0 MPa, diethylene glycol liquid space velocity 0.2 h -1 The product was analyzed by gas chromatography. Figure 3 Experimental results: After the reaction, the conversion rate of diethylene glycol was 98.7 mol%, and the selectivity of morpholine was 98.35 mol%.
[0177] In order to more intuitively illustrate the parameters corresponding to the various components of the catalyst in each embodiment and comparative example, the catalyst conditions of the specific embodiments and comparative examples are summarized as shown in the following table:
[0178]
[0179]
[0180] The molar ratios of catalyst preparation process parameters and catalyst component parameters in the table have been converted according to the masses in the examples.
[0181] It can be seen from the above table that the optimal ratio of the catalyst is, by weight percentage, 75% to 80% of the Y3Si2C2-SiC carrier, 10% to 12% of Cu, and 10% to 15% of Ni.
[0182] By changing the single factor variable in the catalyst preparation process, it can be seen that the higher the impregnation temperature, the better. When the impregnation temperature is 80-100℃, the corresponding catalyst has better catalytic activity and diethylene glycol selectivity for catalyzing diethylene glycol to synthesize morpholine. The longer the impregnation time, the better. When the impregnation temperature is 12-24h, the corresponding catalyst has better catalytic activity and diethylene glycol selectivity for catalyzing diethylene glycol to synthesize morpholine. Similarly, when the calcination temperature is 580-620℃ and the calcination time is 4-6 hours, the corresponding catalyst has better catalytic activity and diethylene glycol selectivity for catalyzing diethylene glycol to synthesize morpholine.
Claims
1. A method for preparing a catalyst for morpholine by a diethylene glycol method, characterized in that: 1) Y3Si2C2-SiC multilayer ceramic carrier is prepared by using yttrium-containing salt and SiC by molten salt method and SPS sintering; 2) Preparing a nickel metal precursor and a copper metal precursor into an aqueous solution, and impregnating the Y3Si2C2-SiC multilayer ceramic carrier into the aqueous solution in a reactor containing the aqueous solution; 3) After the impregnation, the product is filtered, dried, reduced in H2 atmosphere, and calcined to obtain a multilayer ceramic loaded nickel-copper Ni-Cu@Y3Si2C2-SiC catalyst; the impregnation temperature is 80-100°C, the impregnation time is 12-24h, and the impregnation process is carried out in a continuous stirring manner in the early stage; the calcination temperature is 580-620°C, the calcination time is 4-6 hours, and the calcination atmosphere is a nitrogen atmosphere; the components of the catalyst are calculated by weight percentage, the Y3Si2C2-SiC carrier is 75% to 80%, Cu is 10% to 12%, and Ni is 10% to 15%; The preparation process of Y3Si2C2-SiC multilayer ceramic carrier is as follows: 1) According to the molar ratio of each element of Y3Si2C2, a yttrium-containing salt, SiC and sodium chloride are heated and melted at a certain temperature for reaction, and then the product is washed with deionized water until it is neutral, and then vacuum dried to obtain product 1; the yttrium-containing salt is yttrium nitrate hexahydrate, the reaction temperature is 580-620°C, and the reaction time is 1.5-2.5h; 2) crushing the product 1 and mixing it with SiC at a molar ratio of 1:4, and then performing SPS sintering to obtain a Y3Si2C2-SiC multilayer ceramic carrier, wherein the SPS sintering is performed in an Ar gas atmosphere; the SPS sintering temperature is 880-920°C, the sintering time is 8-12 minutes, and the sintering pressure is 48-52MPa; The inner surfaces of the first liner (101) and the second liner (201) used in the reactor are both provided with impact pieces; the impact pieces are spiral ridges (102) or spiral grooves (202) provided on the inner surfaces of the linings; the spiral ridges (102) are provided with pits (103), or the spiral grooves (202) are provided with convex points (203).
2. The method for preparing a catalyst for morpholine by diethylene glycol method according to claim 1, wherein: The heating and melting reaction temperature is 600° C., and the reaction time is 2 h; the SPS sintering temperature is 900° C., the sintering time is 10 min, and the sintering pressure is 50 MPa.
3. The method for preparing a catalyst for morpholine by diethylene glycol method according to claim 1, wherein: The precursor of the nickel metal is selected from nickel nitrate, nickel sulfate, nickel acetate or other nickel salts soluble in water, and the precursor of the copper metal is selected from copper nitrate, copper sulfate, copper acetate or other copper salts soluble in water.
4. The method for preparing a catalyst for morpholine by diethylene glycol method according to claim 1, characterized in that: The drying temperature is 80-120°C, and the reduction temperature is 480-520°C.
5. The method for preparing a catalyst for morpholine by diethylene glycol method according to claim 4, characterized in that: The drying temperature is 100°C, and the reduction temperature is 500°C.
6. The method for preparing a catalyst for morpholine by diethylene glycol method according to claim 1, characterized in that: The Y3Si2C2-SiC multilayer ceramic carrier is in powder, granular or extruded strip form.
7. A catalyst for preparing morpholine by a diethylene glycol process, prepared by the method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Dewatering catalyst and application thereof in preparing morpholine
CN102489282B
Catalyst for synthesizing morpholine by gas-solid phase catalysis and preparation method thereof
CN103962144A
Catalyst required for coproducing N-methyl morpholine and morpholine
CN1911505A
Catalyst for dry reforming reaction of methane, and preparation method and application thereof
CN110813341A